Gerakan PELITA “Peduli Gizi Balita” Di Desa Lengkong Kecamatan Mojoanyar Wilayah UPT Puskesmas Gayaman Kab. Mojokerto - Rina Nur Hidayati; Faisal Ibnu (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
One of the health indicators that is assessed for the success of its achievement of the SDGs (Sustainable Development Goals) is the nutritional status of children under five. The family has an important role in improving and monitoring the nutritional status of children under five. The purpose of this community service is to increase the ability of families to deal with malnutrition in children under five through the PELITA Movement "Care for Children Under-Nutrition". The community service of the PELITA Movement in Lengkong Village, Mojoanyar District, UPT Working Area, Gayaman Health Center, Mojokerto Regency will be held in June-December 2024. The target of the PELITA Movement is 22 families with under-nutrition children under five. The implementation method of this activity includes the preparation, implementation, and evaluation stages. The preparation stage is carried out through permits to the village and socialization to families with under-nutrition of children under five. The implementation stage is fulfilled, to pre-test the family's ability to handle under-nutrition in children under five. The PELITA movement is given through nutrition education and coaching to families through home visits. The final stage is an evaluation (post-test) to determine the family's ability to handle under-nutrition children under five. Family ability increased by 63.6% to good. There was an influence of the PELITA Movement in improving the ability of families to overcome under-nutrition in children under five (P-value 0.001<0.05). Public health nurses can use the PELITA movement approach to accelerate the handling and decrease of nutritional problems for children under five. Keywords : Children Under Five; Under-Nutrition; Ability, PELITA